Hypothalamic free fatty acid receptor-1 regulates whole-body energy balance - Nathalia R.V. Dragano; Edward Milbank; Roberta Haddad-Tóvolli; Pablo Garrido-Gil; Eva Nóvoa; Marcos F. Fondevilla; Valentina Capelli; Ariane Maria Zanesco; Carina Solon; Joseane Morari; Leticia Pires; Ánxela Estevez-Salguero; et al. (Elsevier, 2024)
Objective: Free fatty acid receptor-1 (FFAR1) is a medium- and long-chain fatty acid sensing G protein-coupled receptor that is highly expressed in the hypothalamus. Here, we investigated the central role of FFAR1 on energy balance. Methods: Central FFAR1 agonism and virogenic knockdown were performed in mice. Energy balance studies, infrared thermographic analysis of brown adipose tissue (BAT) and molecular analysis of the hypothalamus, BAT, white adipose tissue (WAT) and liver were carried out. Results: Pharmacological stimulation of FFAR1, using central administration of its agonist TUG-905 in diet-induced obese mice, decreases body weight and is associated with increased energy expenditure, BAT thermogenesis and browning of subcutaneous WAT (sWAT), as well as reduced AMP-activated protein kinase (AMPK) levels, reduced inflammation, and decreased endoplasmic reticulum (ER) stress in the hypothalamus. As FFAR1 is expressed in distinct hypothalamic neuronal subpopulations, we used an AAV vector expressing a shRNA to specifically knockdown Ffar1 in proopiomelanocortin (POMC) neurons of the arcuate nucleus of the hypothalamus (ARC) of obese mice. Our data showed that knockdown of Ffar1 in POMC neurons promoted hyperphagia and body weight gain. In parallel, these mice developed hepatic insulin resistance and steatosis. Conclusions: FFAR1 emerges as a new hypothalamic nutrient sensor regulating whole body energy balance. Moreover, pharmacological activation of FFAR1 could provide a therapeutic advance in the management of obesity and its associated metabolic disorders.